1999
DOI: 10.1191/026921599677086409
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceptions of the Odstock Dropped Foot Stimulator (ODFS)

Abstract: The ODFS was perceived by the users to be of considerable benefit. A comprehensive clinical follow-up service is essential to achieve the maximum continuing benefit from FES-based orthoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
97
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 7 publications
3
97
0
1
Order By: Relevance
“…Clinical advancements made possible by NP technology include those that restore hearing (Clark et al, 1977;Kessler, 1999;Spelman, 1999), respiration (DiMarco, 2001), bladder voiding (Brindley et al, 1982;Grill et al, 2001), and upper and lower extremity control (Kraft et al, 1992;Kralj et al, 1988;Liberson et al, 1961;Prochazka et al, 1997;Taylor et al, 1999;Weingarden et al, 1998). A subset of these prostheses communicates with neural tissue via penetrating multiple-electrode arrays (MEAs), which can provide highly specific and robust activation of the targeted neurons (Branner et al, 2001;Hillman et al, 2003;McDonnall et al, 2004;Tyler and Durand, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical advancements made possible by NP technology include those that restore hearing (Clark et al, 1977;Kessler, 1999;Spelman, 1999), respiration (DiMarco, 2001), bladder voiding (Brindley et al, 1982;Grill et al, 2001), and upper and lower extremity control (Kraft et al, 1992;Kralj et al, 1988;Liberson et al, 1961;Prochazka et al, 1997;Taylor et al, 1999;Weingarden et al, 1998). A subset of these prostheses communicates with neural tissue via penetrating multiple-electrode arrays (MEAs), which can provide highly specific and robust activation of the targeted neurons (Branner et al, 2001;Hillman et al, 2003;McDonnall et al, 2004;Tyler and Durand, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This research has provided evidence of the positive benefits of the application of FES, namely reduction in energy expenditure, increased gait velocity, decreased falls and improved quality of life (Taylor et al, 1999a;1999b;Burridge, 2001;Kottink et al, 2004;Robbins et al, 2006;Laufer et al, 2009; National Institute for Health and Clinical Excellence, 2009). The National Guidelines for Stroke propose that FES should only be considered when an ankle foot orthosis (AFO) does not adequately control the dropped foot and when obvious gait improvements can be demonstrated (Royal College of Physicians, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A service review by Taylor et al (1999a) in 1999 concluded that their service met the needs of past and present users. Background information was provided on the number of patient appointments, follow-up procedure and inclusion/ exclusion criteria of their service.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations